Leadership Management Styles: An Imperative for Employee Motivation Among GSM Service Providers in Port Harcourt - Rotimi Akinnuoye (American Journal of Economics and Business Management, 2021)
The aim of this research was to empirically unravel the strategic prowess of leadership management styles employee motivation issues, as it concerns GSM operators in Port Harcourt. The study used cross-sectional survey design in structured questionnaire to collect data from 400 employees of GSM firms. A total of 3 hypotheses were proposed and statistically tested with Spearman’s Correlation Coefficient tool, aided by SPSS version 23.0. Results revealed that participatory leadership has a positive and significantly relationship with employee motivation. However, autocratic leadership had a positive but weak relationship with employee motivation. Based on these findings, this research concluded that participative leadership is a veritable management tool that can help in the motivation of employees of the organization. In this light, the research recommended that management and staffs of GSM operators, especially those in the position of leadership should embraced participatory leadership management style as strategy of employees’ motivation. Also, strategists of telecommunication firms should be less or if possible, circumvent autocratic leadership management style in order to sustain employees’ motivation.